The Effect of TiO2 Loading on Nanocellulose (NC)/TiO2 Solid Composite and pH on Paracetamol Photodegradation - Dwita Suastiyanti, Praswasti P.D.K. Wulan, Athanasia A. Septavani, Khumaeroh, Annisa Nurul Syabila, Ratnawati (South Eastern European Journal of Public Health, 2025)
These days, organic contaminants from the pharmaceutical industry are a constant global issue that pollute water supplies. This study examined the effects of pH on the photodegradation of paracetamol and TiO2 loading on the synthesis of NC/TiO2 solid composites (NCT) as a photocatalyst. Low concentration of acid is used on hydrolysis to extract nanocellulose from empty palm oil bunches (EPOB), and SEM analysis shows that the impregnation approach produced NCT effectively. The optimal conditions for photodegradation of waste containing 15 ppm paracetamol with a concentration reduction of up to 60% for 4 hours are provided by NCT with TiO2 loading of 70% on nanocellulose (NCT 30-70) as much as 1 g/L at pH 6. Reusing photocatalyst demonstrates a 13% reduction in photocatalyst ability up to 4 cycles.